2000
DOI: 10.1097/00001721-200010000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the search for thrombophilia risk factors among antiphospholipid syndrome patients with thrombosis

Abstract: Thrombosis is a major clinical feature of the antiphospholipid syndrome. Interactions between genetic and acquired factors could contribute to thrombosis development. In this study, we evaluated 40 patients with antiphospholipid syndrome and thrombosis, 31 primary and nine secondary to systemic lupus erythemathosus, to estimate the carrier rates of factor V Leiden, 20210A --> G prothrombin variant and 677C --> T in the MTHFR gene. Protein C, protein S and antithrombin were measured in 30 patients, with a media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…In a series of 152 aPL-positive patients, Galli et al (Galli et al, 2000) did not find an association between the C677T MTHFR polymorphism alone or in combination with either Factor V Leiden or G20210A prothrombin polymorphisms and thrombosis. Similar results were obtained by Torresan et al (Torresan et al, 2000) in 30 patients with APS in whom no significant variation was found between the patient group and the controls regarding the prevalence of homozygotes for the mutated 677T allele (2.5% vs. 5.4%), and by Forastiero et al (Forastiero et al, 2001) in 105 aPL-positive patients in whom the frequencies of the C677T MTHFR alleles were not different either between the aPL groups and normal controls or between APS and non-APS groups. In addition, cerebrovascular disease was not related to homozygous or heterozygous C677T MTHFR polymorphism in 44 primary APS patients (Kalashnikova et al, 2005).…”
Section: Methylenetetrahydrofolate-reductase (Mthfr) C677t/a1298csupporting
confidence: 92%
See 1 more Smart Citation
“…In a series of 152 aPL-positive patients, Galli et al (Galli et al, 2000) did not find an association between the C677T MTHFR polymorphism alone or in combination with either Factor V Leiden or G20210A prothrombin polymorphisms and thrombosis. Similar results were obtained by Torresan et al (Torresan et al, 2000) in 30 patients with APS in whom no significant variation was found between the patient group and the controls regarding the prevalence of homozygotes for the mutated 677T allele (2.5% vs. 5.4%), and by Forastiero et al (Forastiero et al, 2001) in 105 aPL-positive patients in whom the frequencies of the C677T MTHFR alleles were not different either between the aPL groups and normal controls or between APS and non-APS groups. In addition, cerebrovascular disease was not related to homozygous or heterozygous C677T MTHFR polymorphism in 44 primary APS patients (Kalashnikova et al, 2005).…”
Section: Methylenetetrahydrofolate-reductase (Mthfr) C677t/a1298csupporting
confidence: 92%
“…However, from the first case of SLE-associated APS in a young female homozygous for the 20210A allele in the prothrombin gene who developed venous thrombosis while taking oral contraceptives (Sivera et al, 2000), several subsequent studies have demonstrated an association between the prothrombin G20210A polymorphim and thrombosis in APS patients. Torresan et al found in 30 Brazilian patients with APS and thrombosis a higher prevalence of the 20210A allele of the prothrombin gene when compared with controls individuals (5% vs. 0,7%) (Torresan et al, 2000). Similarly, Forastiero et al found in 105 Caucassian consecutive unselected patients with aPL grouped as having APS (n= 69) and not having APS (n= 36) that the 20210A allele was significantly more frequent in APS patients than in healthy controls subjects (8,7% vs. 2%) (Forastiero et al, 2001).…”
Section: Prothrombin Gene Mutation and Risk Of Thrombosismentioning
confidence: 97%
“…We could not find any published controlled studies investigating the actual frequency of natural anticoagulant deficiencies in patients with APS. Torresan et al [25] evaluated 30 APS patients with thrombosis and all of those patients were found to have normal protein C, protein S and antithrombin activity levels. In our study, we investigated protein C, protein S, and antithrombin activities in 94 APS patients with thrombosis, 40 aPLA-positive patients without thrombosis and 120 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Avivi et al [44] found elevated plasma homocyteine levels in onethird of APS patients, Seriolo et al [45] demonstrated that plasma homocyteine levels are significantly higher in aPLpositive rheumatoid arthritis (RA) patients with thrombosis compared with aPL-positive RA patients without thrombosis, and Ames et al [46,47] suggested that higher plasma homocysteine levels and methylenetetrahyrofolate reductase (MTHFR) mutation may influence the age of first event and the number of events in aPL-positive patients. Torresan et al [48] suggested that prothrombin (Factor II) G20210 mutation increases the risk for thrombosis in aPL-positive patients, a finding was not supported by other studies [49,50]. In addition, Torresan et al [48] reported that FVL mutation, MTHFR mutation, or protein C, protein S, and antithrombin III deficiencies are not associated with increased risk for thrombosis in aPL-positive patients.…”
Section: Introductionmentioning
confidence: 94%
“…Torresan et al [48] suggested that prothrombin (Factor II) G20210 mutation increases the risk for thrombosis in aPL-positive patients, a finding was not supported by other studies [49,50]. In addition, Torresan et al [48] reported that FVL mutation, MTHFR mutation, or protein C, protein S, and antithrombin III deficiencies are not associated with increased risk for thrombosis in aPL-positive patients.…”
Section: Introductionmentioning
confidence: 94%